Capsular Polysaccharide Expression in Commensal Streptococcus Species: Genetic and Antigenic Similarities to Streptococcus pneumoniae - Skov Sørensen, Uffe B. (mBio, 2016)
Expression of a capsular polysaccharide is considered a hallmark of most invasive species of bacteria, including Streptococcus pneumoniae, in which the capsule is among the principal virulence factors and is the basis for successful vaccines. Consequently, it was previously assumed that capsule production distinguishes S. pneumoniae from closely related commensals of the mitis group streptococci. Based on antigenic and genetic analyses of 187 mitis group streptococci, including 90 recognized serotypes of S. pneumoniae, we demonstrated capsule production by the Wzy/Wzx pathway in 74% of 66 S. mitis strains and in virtually all tested strains of S. oralis (subspecies oralis, dentisani, and tigurinus) and S. infantis. Additional analyses of genomes of S. cristatus, S. parasanguinis, S. australis, S. sanguinis, S. gordonii, S. anginosus, S. intermedius, and S. constellatus revealed complete capsular biosynthesis (cps) loci in all strains tested. Truncated cps loci were detected in three strains of S. pseudopneumoniae, in 26% of S. mitis strains, and in a single S. oralis strain. The level of sequence identities of cps locus genes confirmed that the structural polymorphism of capsular polysaccharides in S. pneumoniae evolved by import of cps fragments from commensal Streptococcus species, resulting in a mosaic of genes of different origins. The demonstrated antigenic identity of at least eight of the numerous capsular polysaccharide structures expressed by commensal streptococci with recognized serotypes of S. pneumoniae raises concerns about potential misidentifications in addition to important questions concerning the consequences for vaccination and host-parasite relationships both for the commensals and for the pathogen.